Source, bioavailability, and toxicity of metals in modern fjord sediments, west Spitsbergen, and their influence on sediment-associated biota - Choudhary, Shabnam; Syed Mohammad, Saalim; Mohan, Rahul; Tiwari, Manish (Frontiers in Marine Science, 2024)
Metal contamination in the Arctic region has increased over the years despite its remote and isolated location. Thus, to evaluate the bioavailable fractions of various metals and their effects on sediment-associated biota, the surface sediments from the fjords were analyzed for bulk concentration of metals and their speciation in different fractions. Metals concentrations were higher in the inner fjord region and decreased towards the outer fjord, supported by the terrigenous influence (TI%) calculated. Cr and Pb showed higher excess values attributed to their additional source other than the catchment rocks. So, to assess the metal-related ecological risk, the bulk concentration of metals was compared with Arctic sediment quality guidelines (ASQGs). Cr, Cd, and Pb concentrations were high, indicating potential adverse biological effects in the area. To avoid the risk of overestimation, metal speciation was conducted, showing that overall metal concentrations were higher in the residual fraction; however, higher concentrations of Mn in labile phases pose a moderate risk to the sediment-associated biota. Additionally, the population density of foraminifera in the sediments was calculated to assess the influence of bioavailable metal on benthic foraminifera. It was found that the presence of metals in bioavailable fractions affected the abundance of the foraminifera. However, no morphological abnormalities were observed in the species